Futures of Natural Resources : Book of Abstracts of the 24th Futures Conference, 4 June Online and 13-14 June 2024, Turku, Finland - Ranaweera, Lahara; Saarimaa, Riikka (Turun yliopisto, 2025)
Futures conference 2024 focused on the questions of what futures research provides for the sustainable management of natural resources, both in water and the surface of the earth and below. How can we maintain a good quality of life on earth when we are facing increasing pressures on natural resources? Can technology reduce the current wasteful use of natural resources and how? What kinds of new approaches, through political and ecological economics could be brought to the management of natural resources in the future?  What kind of novel approaches and solutions could futures research and its methodology offer in the wider societal discussion?
The conference program consisted of keynote lectures, parallel paper sessions and participatory workshops. The conference generated multidisciplinary, stimulating and critical discussions that promoted networking between people interested in futures issues from different backgrounds and perspectives.